Length and time scale divergences at the magnetization-reversal transition in the Ising model. - Stinchcombe, R; Misra, A; Chakrabarti, B (1999)
The divergences of both the length and time scales, at the magnetization-reversal transition in the Ising model under a pulsed field, have been studied in the linearized limit of the mean field theory. Both the length and time scales are shown to diverge at the transition point and it has been checked that the nature of the time scale divergence agrees well with the result obtained from the numerical solution of the mean field equation of motion. Similar growths in length and time scales are also observed, as one approaches the transition point, using Monte Carlo simulations. However, these are not of the same nature as the mean field case. Nucleation theory provides a qualitative argument that explains the nature of the time scale growth. To study the nature of growth of the characteristic length scale, we have looked at the cluster size distribution of the reversed spin domains and have defined a pseudocorrelation length that has been observed to grow at the phase boundary of the transition.